The Lived Experiences of Transition from College to University in Scotland: A Qualitative Research Synthesis - Robertson, Derek J.; Cunningham, Tom (International Journal of Educational and Life Transitions, 2023)
The Scottish Government has recently accepted the recommendations of the Scottish Funding Council to move towards a coherent tertiary education and skills system. This is one where colleges and universities in Scotland accelerate and deepen their collaboration to provide fair, flexible, and sustainable learner journeys. This paper provides a timely summary and analysis of what is known about the lived experiences of those involved in making effective transitions from college to university in Scotland. Previous project work has identified this transition as problematic, suggesting an academic ‘deficit model’ of college students transitioning to university. This qualitative research synthesis seeks to move beyond this to identify common themes from published literature to inform learning and teaching practice in both colleges and universities in Scotland. These themes include the sectoral, academic, personal and logistical factors that influence making effective transitions. We raise key topics for discussion in relation to the development of a coherent tertiary sector: (1) Responsibility for Transition, (2) Alignment between Colleges and Universities and, (3) Widening Participation. While our findings will have clear implications for those in the Scottish sector, more broadly it also has implications for all those considering relationships in, and between, further and higher education.